PEMBELAJARAN PKN MELALUI BERITA DI MEDIA MASSA - Santoso, Puji (Institut Agama Islam Negeri Kediri, 2017)
Abstract: The students in class X 2 of MAN 3 Kediri generally consider PKN less important lesson. As a result, the students are reluctant to know the material. In class, they become passive, unexcited, and have difficulty in understanding the material of PKN given by the teacher. Therefore, special learning strategyis needed to enhance students’ motivation to learn PKN materials. Learning strategy in this study is “In The News”. The procedure of“In The News approach” is that students are divided into groups in which each group has to bring articles, headlines, editorials or certain caricatures as teachers expected. Each group chooses one article of their interest to be presented and discussed; Another student noted the key points of the presentation the discussion. The research data shows that an increase in students’ motivation and comparedto the results of the previous and the last cycle. Thus we can conclude that from the aspect of affective (motivation) approaches used have positive impact. Abstrak: Para siswa, di kelas X-2 MAN 3 Kediri, umumnya menganggap pelajaran PKN kurang penting. Akibatnya adalah siswa menjadi tidak mau tahu akan materi PKN. Di kelas, kondisi siswa menjadi pasif, tidak bersemangat, dan kesulitan memahami materi pelajaran PKN yang diberikan oleh guru. Oleh sebab itu, diperlukan strategi pembelajaran khusus yang mampu meningkatkan motivasi belajar siswa dalam mengikuti pelajaran PKN. Strategi pembelajaran dalam penelitian ini adalah “In The News”. Prosedur dari pendekatan “In The News” adalah siswa dibagi menjadi kelompok; setiap kelompok membawa artikel, pokok berita, editorial atau karikatur tertentu sesuai dengan yang diperintah guru; setiap kelompok memilih satu artikel yang menarik untuk dipresentasikan dan didiskusikan; siswa yang lain mencatat poin-poin penting dari presentasi diskusi tersebut. Data dalam penelitian memperlihatkan bahwa terjadi peningkatan motivasi siswa dibandingkan antara hasil prasiklus dan siklus terakhir. Dengan demikian dapat disimpulkan bahwa dilihat dari aspek afektif (motivasi) pendekatan yang digunakan dapat berdampak positif.